The structure of the proton and the combination of fundamental forces - Gimsa, Andreas (International Journal of Scientific Research and Management (IJSRM), 2024)
This publication deals with the structure of the proton and the three fundamental forces: strong force, electromagnetic force and gravitational force. It can be shown that these fundamental forces have an electromagnetic origin.